Demographic, socioeconomic, and attitudinal associations with children's cycle-helmet use in the absence of legislation. Issue 5 (4th October 2007) - Lang, Iain A
Abstract : The association of demographic, socioeconomic, and attitudinal factors with children's cycle-helmet use was investigated using self-reported data from 9775 children aged 8–12 in England, where there are currently no legal requirements that cyclists (of any age) wear helmets. The results suggest that demographic factors, socioeconomic status, and attitudes influence whether children wear bicycle helmets but that attitudinal factors are most important.